Biomechanical investigation of the effect of Vitamin C supplementation on Osseointegration of titanium implants in rat (Rattus norvegicus) tibia - Kaya, Can Ayhan; Tanrisever, Murat; Duger, Nurullah; Yildirim, Tuba Talo; Ozcan, Erhan Cahit; Kan, Umit Koray; Dundar, Serkan (Univ Zulia, Facultad Ciencias Veterinarias, 2025)
In this study, it was aimed to evaluate some possible effects of vitamin C supplementation on the osseointegration process implants placed in rat tibias. Thirty 3-month-old female Spraque Dawley rats (Rattus norvegicus) were divided into 3 groups. In all groups, the corticocancellous part of the the metaphysis of the right tibia bones were surgically reached. Monocortical implant sockets were created by surgical methods under serum cooling, and then titanium implants with 2.5 mm diameter and 4 mm long titanium were integrated on these bone sockets. Group Sham (Control) (n=10): No additional application was made during the experimental process. Group C1 (n=10): 5 mg/kg vitamin C was given to the rats with oral gavage application in three days a week for four weeks of experimental process. Group C2 (n=10): 10 mg/kg vitamin C was given to the rats with oral gavage application in three days a week for four weeks of experimental process. At the end of the four- week experimental setup, all rats were sacrificed and the experimental process was completed. The implants integrated in the tibias of all rats were collected with the surrounding bone tissue after removing the soft tissues for biomechanical analysis. Biomechanical reverse torque analysis was applied to all implants. Statistical analysis of the obtained data; Kruskall- Wallis test, no statistically significant difference was detected between the control and experimental groups (P>0,05). In conclusion, 5 and 10mg/kg vitamin C supplementation has no positive or negative effects on osseointegration. This situaiton can be explained in two ways; the first, the dosages of vitamin C used in this study is not sufficient to create an effect. Second, the endogenous synthesis of this vitamin is enough even though under these stress conditions.
Investigación biomecánica del efecto de la suplementación con vitamina C sobre la osteointegración de implantes de titanio en tibias de rata (Rattus norvegicus)
Keywords: Vitamin C; osseointegration; rat tibias